Transformation of Village Governance in Archipelagic Regions: The Role of Local Government Policy Innovation in Overcoming Access and Infrastructure Constraints - Muksin, Isra; Losung, Olviyani; Rusman, Sunarti; Jabid, Fiyona (Pt. Anagata Sembagi Education, 2026)
This study examines the transformation of village governance in archipelagic regions, which are often characterized by geographical isolation, limited infrastructure, and restricted access to public services. These structural challenges necessitate innovative policy interventions from local governments to enhance governance effectiveness and support sustainable development. This research employs a qualitative approach with a descriptive-analytical design, utilizing secondary data derived from a systematic literature review of relevant scholarly articles, policy documents, and empirical case studies. Data were collected through documentation techniques and analyzed using qualitative content analysis and comparative methods to identify patterns of policy innovation and their impacts on governance transformation. The findings reveal that local government policy innovations—such as adaptive spatial planning (RDTR), tourism-based development, collaborative governance, BUMDes innovation, and digital governance systems (SPBE) play a significant role in improving access to services, strengthening infrastructure, and enhancing institutional capacity. However, challenges such as limited ICT infrastructure, weak coordination, and low human resource capacity remain critical barriers. The study concludes that an integrated and adaptive governance approach, supported by strong institutional capacity and multi-stakeholder collaboration, is essential for achieving sustainable and inclusive governance transformation in archipelagic villages.